The ontological conceptions as an access point to the Social Sciences and their diverse methodological perspectives - Soto Kiewit, Luis Diego (2020)
This article proposes the reading of ontological conceptions as a way of approaching and accessing the distances and discrepancies of the different perspectives of the social sciences. The objective is to identify how epistemological and methodological distances can be understood from the notion of reality on which knowledge proposals are based. The reflection includes a dialogue with two methodological perspectives of the social sciences, this to exemplify how the ontological foundations allow us to understand affirmations or positions in more abstract reflective levels, which we will call here: higher levels. For this demonstrative exercise, constructivist and post-structuralism structuralism are considered.